1995
DOI: 10.1111/j.1432-1033.1995.238_1.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster of Structural and Regulatory Genes for Light‐Induced Carotenogenesis in Myxococcus xanthus

Abstract: In the bacterium Myxococcus xanthus, several genes for carotenoid synthesis lie together at the carAcarB chromosomal locus and are co-ordinately activated by blue light. A 12-kb DNA stretch from wildtype M. xanthus has been sequenced that includes the entire carA-carB gene cluster. According to sequence analysis, the cluster contains 11 different genes. Intergenic distances are very short or nil (implying translational coupling), giving further support to previous evidence indicating that most (or all) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 74 publications
2
81
0
Order By: Relevance
“…Combining gene expression and disruption analysis, we confirmed that dr0091 and dgeo2309 encode a novel carotenoid 1,2-hydratase in D. radiodurans and D. geothermalis. The genes dr0091 and dgeo2309 showed little homology to the CrtC-type carotenoid 1,2-hydratase, which is found mainly in photosynthetic bacteria (Armstrong et al, 1989;Frigaard et al, 2004;Giraud et al, 2004;Kovács et al, 2003;Lang et al, 1995;Ouchane et al, 1997;Scolnik et al, 1980) and in the non-photosynthetic bacterium Myxococcus xanthus (Botella et al, 1995). Recently, a carotenoid 1,2-hydratase homologue of DR0091 and Dgeo2309 from the cyanobacterium Synechococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Combining gene expression and disruption analysis, we confirmed that dr0091 and dgeo2309 encode a novel carotenoid 1,2-hydratase in D. radiodurans and D. geothermalis. The genes dr0091 and dgeo2309 showed little homology to the CrtC-type carotenoid 1,2-hydratase, which is found mainly in photosynthetic bacteria (Armstrong et al, 1989;Frigaard et al, 2004;Giraud et al, 2004;Kovács et al, 2003;Lang et al, 1995;Ouchane et al, 1997;Scolnik et al, 1980) and in the non-photosynthetic bacterium Myxococcus xanthus (Botella et al, 1995). Recently, a carotenoid 1,2-hydratase homologue of DR0091 and Dgeo2309 from the cyanobacterium Synechococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…One module, pI, is an 18-bp segment upstream of the promoter that displays dyad symmetry, with 6-bp repeats flanking a 6-bp intervening stretch. The design of this module resembles in some respects that reported previously for the operator of MerR, the prototypical member of a family of transcriptional regulators whose DNA binding domain shows sequence similarity to the N-terminal domain of CarA (16). In the absence of Hg(II), MerR represses expression of the mercury resistance operon merTP(C)AD but activates its expression when Hg(II) is present.…”
Section: Discussionmentioning
confidence: 83%
“…One corresponds to the single gene crtI and the other to an operon, carB, where the rest of the structural genes are grouped Botella et al, 1995). The precise mechanism for the light activation of the crtI promoter (P I ) differs from that of the carB promoter (P B ).…”
Section: Introductionmentioning
confidence: 99%